INTEGRATION OF SUSTAINABILITY INDICATORS IN URBAN FORMATION: A GAP ANALYSIS - Taiwo, Ogungbenro Matthew; Samsudin, Salfarina; @ Zulkarnain Daud, Dzurllkanian; Ayodele, Olukolajo Michael (PLANNING MALAYSIA, 2021)
Cities and urban centers are made for people and not vice versa. However, many policies on urban formation fail to take cognisance of human factors in their design and planning. Restructuring of cities to accommodate the economics and environmental demand of urbanisation alters the organic urban form. Modernists often concentrate on road construction, fresh air circulation, light, space, space for vehicles, etc., but ignore city architecture's social dimension. This study explores the psychological aspect of cities and housing due to the trends in the land-use change in sustainable city agenda with specific reference to Ibadan City. This work is an extract of research on the community perspective of land-use change on social sustainability. Data were collected through a structured questionnaire from 397 residents of the Central Local Government and analysed using Partial Least Square - Structural Equation Modelling (PLS-SEM) and Relative Importance Index (RII). The results show the urban form characterised by land-use change and its consequential effects on social sustainability. The alteration of the urban form through land-use changes by individual landowners' decisions impacts others' social sustainability. It was recommended that policymakers incorporate the sustainable social elements into the planning procedure.